Faktor Penyebab Rendahnya Kesadaran Masyarakat Terhadap Pendidikan di Desa Mulyosari Kecamatan Pagerwojo Kabupaten Tulungagung - Ida Faridatul Maskhuroh; Mohammad Hasib (Journal of Knowledge and Collaboration, 2025)
This research aims to analyze the factors contributing to the low public awareness of education in Mulyosari Village, Pagerwojo District, Tulungagung Regency. Employing a descriptive qualitative method, data was collected through in-depth interviews, observations, and documentation studies involving parents, school-aged children, and community leaders. The findings indicate that public awareness of education remains relatively low, despite a conceptual understanding of its importance. The primary contributing factors include limited family economic conditions , lack of intrinsic motivation from children to learn , insufficient parental support , the influence of peers and a social environment that prioritizes work , cultural stigma and gender stereotypes that deem education unimportant, especially for females , and the phenomenon of early marriage. Although the village government has made efforts such as providing assistance and conducting socialization , these complex obstacles necessitate a holistic and sustainable approach to change mindsets and increase educational participation in the village.